2022-RA-698-ESGO Survival outcomes of patients with vaginal melanoma: an institutional case series and a systematic review with IPD analysis. (20th October 2022) - Zachariou, Eleftherios; Pergialiotis, Vasilios; Prokopakis, Ioannis; Vlachos, Athanasios; Haidopoulos, Dimitrios; Rodolakis, Alexandros; Thomakos, Nikolaos
Abstract : Introduction/Background: Vaginal melanoma is a rare form of gynecologic malignancy that that accounts for approximately 0.2% of all melanomas. Survival rates reported in large multi-institutional studies report a recurrence-free survival rates that exceed 70% in 5 years and mean overall survival rates thar range between 4 and 5 years. In the present case series and systematic review we accumulate current evidence in the field. Methodology: We performed a retrospective chart review of vaginal melanoma patients treated in our hospital as well as a systematic review of the literature using Medline, Scopus, Clinicaltrials.gov, EMBASE, Cochrane Central Register of Controlled Trials CENTRAL and Google Scholar databases investigating for individual patient data that could be used for survival analyses Results: Overall, 124 patients were retrieved from international databases and 6 patients with primary vaginal melanoma were identified from the retrospective chart reviews of our hospital. The mean progression free survival time of patients retrieved from the literature search was 19.2 months (95% CI 11.2, 27.2). The mean overall survival time was 36.2 months (95% CI 22.8, 49.6). At 5 years only 7% of patients (9/107) were alive. Only 3 patients were free of disease at 5 years. Conclusion: Survival outcomes of patient with vaginal melanoma are poor as the disease is associated with short intervals to recurrence and high mortality rates. Various treatment strategies have been published throughout the years with novel targeted therapies achieving the best survival rates.